Optimal asset allocation for interconnected life insurers in the low interest rate environment under solvency regulation - Tobias Niedrig (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
I assess how Basel III, Solvency II and the low interest rate environment will affect the financial connection between the bank and insurance sector by changing the funding patterns of banks as well as the investment strategies of life insurance companies. Especially for life insurance companies, the current low interest rate environment poses a key risk since declining returns on investments jeopardize the guaranteed return on life insurance contracts, a core component of traditional life insurance contracts in several European countries. I consider a contingent claim framework with a direct financial connection between banks and life insurers via bank bonds. The results indicate that life insurers' demand for bank bonds increases over the mid-term but ultimately declines in the long-run. Since life insurers are the largest purchasers of bank bonds in Europe, banks could lose one of their main funding sources. In addition, I show that shareholder value driven life insurers' appetite for risk increases when the gap between asset return and liability growth diminishes. To check the robustness of the findings, I calibrate a prolonged low interest rate scenario. The results show that the insurer's risk appetite is even higher when interest rates remain persistently low. A sensitivity analysis regarding industry-specific regulatory safety levels reveals that contagion between bank and life insurer is driven by the insurers' demand for bank bonds which itself depends on the regulatory safety level of banks.
Keywords: G11; G18; G22; G28; 330; Basel III; Solvency II; Life Insurance; Interest Rate Guarantees; Asset Allocation; Contagion; Interconnectedness